Moderating effects of student heterogeneity on community of inquiry affective outcomes: A multigroup analysis - Teng Seng Choo; Hazri Jamil; Lei Mee Thien (Computers and Education Open)
This study examines the influence of student background attributes on the relationships between Community of Inquiry (CoI) presences and affective learning outcomes in online courses. Using partial least squares structural equation modeling (PLS-SEM) and multigroup analysis, the study investigated how gender, prior online course experience, and degree level moderate the effects of teaching, cognitive, social, and metacognitive presence on perceived learning and satisfaction. Data were collected from 479 students at a Malaysian public university. Results show that gender and prior experience moderate some relationships between CoI presences and perceived learning, but not perceived satisfaction. Specifically, male students perceive greater learning benefits from metacognitive presence compared with females, while females perceive higher learning from cognitive presence. Students with prior online course experience report significantly higher perceived learning from metacognitive presence compared with inexperienced students. Degree level (undergraduate vs. postgraduate) does not significantly moderate most relationships, though measurement invariance issues were found for teaching presence across degree levels. The findings highlight the importance of considering student subgroup heterogeneity in online education research and practice. The result suggests tailored instructional strategies that consider gender differences and prior online learning experience. This study contributes to a more nuanced understanding of how diverse learners experience and benefit from different aspects of the online learning environment, with implications for course design and delivery.